2020
DOI: 10.1111/evo.14077
|View full text |Cite
|
Sign up to set email alerts
|

Strength in numbers? Cytotype frequency mediates effect of reproductive barriers in mixed‐ploidy arrays

Abstract: When differentiated lineages come into contact, their fates depend on demographic and reproductive factors. These factors have been well-studied in taxa of the same ploidy, but less is known about sympatric lineages that differ in ploidy, particularly with respect to demographic factors. We assessed prezygotic, postzygotic, and total reproductive isolation in naturally pollinated arrays of diploid-tetraploid and tetraploid-hexaploid population mixes of Campanula rotundifolia by measuring pollinator transitions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Their hybrid origin was confirmed in many cases, whereas little is known about their role in enabling gene flow between and introgression into their parental cytotypes (Kolář et al 2017). This is especially true for ploidies higher than tetraploid as studied here; previous studies have mostly focussed on triploids originating in diploid-tetraploid contact zones (Ramsey and Schemske 1998; but see Kolář et al 2009;Greiner and Oberprieler 2012;Sutherland and Galloway 2017;Sutherland et al 2020).…”
Section: Introductionmentioning
confidence: 71%
“…Their hybrid origin was confirmed in many cases, whereas little is known about their role in enabling gene flow between and introgression into their parental cytotypes (Kolář et al 2017). This is especially true for ploidies higher than tetraploid as studied here; previous studies have mostly focussed on triploids originating in diploid-tetraploid contact zones (Ramsey and Schemske 1998; but see Kolář et al 2009;Greiner and Oberprieler 2012;Sutherland and Galloway 2017;Sutherland et al 2020).…”
Section: Introductionmentioning
confidence: 71%
“…Natural selection could also act on floral traits for differentiated pollinator signals (e.g., Nuismer and Cunningham, 2005). For pollinators to act as a mechanism to facilitate coexistence of cytotypes (Kolář et al, 2017;Sutherland et al, 2020;Laport et al, 2021), the flowers of the cytotypes must differ in ways that pollinators can perceive (e.g., Segraves and Thompson, 1999) or have sufficient morphological differences to facilitate isolation (e.g., Borges et al, 2012). For Gymnadenia conopsea (Orchidaceae), cytotypes differ in floral signals, mainly floral scent (Jersáková et al, 2010;Gross and Schiestl, 2015), and assortative mating has also been observed in some populations (Gross and Schiestl, 2015), suggesting that these mechanisms may function as reproductive isolation mechanisms in mixed populations of autotetraploids.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, post-pollination mechanisms of isolation may be more important in keeping polyploids distinctive, as in Aster amellus (Asteraceae) (Castro et al, 2011) and for some species little evidence of reproductive isolation is observed (e.g., Barringer and Galloway, 2017). Although pollinator-mediated reproductive isolation between cytotypes has strong theorical support and empirical evidence for some species where it has been measured (e.g., Kennedy et al, 2006;Thompson and Merg, 2008;Roccaforte et al, 2015;Sutherland et al, 2020;Laport et al, 2021), few studies have examined differences in multifaceted floral signals between cytotypes making generalisations challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Reproductive barriers between parental populations, as well as between those populations and heteroploid hybrids, differed with cytotype, with parental and F1 barriers stronger between diploids and tetraploids than between different polyploids. Pollinators show a preference for rare cytotypes in this system, which increases the likelihood of gene flow between a rare cytotype and a common one in contact zones (Sutherland et al, 2020). This preference, coupled with differences in reproductive barriers across cytotypes, sets up two expectations for C. rotundifolia contact zones.…”
Section: Discussionmentioning
confidence: 99%